Cruelty free : a novel - Glenn, Caroline (William Morrow, 2026)
"For fans of Sarah Langan and Rachel Yoder, a twisted debut horror novel in which a disgraced movie star returns to Hollywood 10 years after the kidnapping of her young daughter intent on seeking revenge"-- Provided by publisher.